Viabilidades térmica, econômica e de materiais de um sistema solar de aquecimento de água a baixo custo para fins residenciais - Costa, Raimundo Nonato Almeida (2014)
An solar alternative system for water heating is presented. Is composed for one low cost alternative collector and alternative thermal reservoir for hot water storing. The collector of the system has box confectioned in composite material and use absorption coils formed for PVC tubes. The box of hot water storage was confectioned from a plastic polyethylene drum used for storage of water and garbage, coated for a cylinder confectioned in fiber glass. The principle of functioning of the system is the same of the conventionally. Its regimen of work is the thermosiphon for a volume of 250 liters water. The main characteristic of the system in considered study is its low cost, allowing a bigger socialization of the use of solar energy. It will be demonstrated the viabilities thermal, economic and of materials of the system of considered heating, and its competitiveness in relation to the available collectors commercially. Relative aspects will be boarded also the susceptibility the thermal degradation and for UV for the PVC tubes. It will be shown that such system of alternative heating, that has as main characteristic its low cost, presents viabilities thermal, economic and of materials